2015
DOI: 10.1186/s12905-015-0209-y
|View full text |Cite
|
Sign up to set email alerts
|

Unmet need of long-acting and permanent family planning methods among women in the reproductive age group in shashemene town, Oromia region, Ethiopia: a cross sectional study

Abstract: BackgroundMany countries continue to have high fertility rates and most of the predicted increase in the world’s population until 2100 comes from these countries. Among family planning methods, Long Acting and Permanent Methods are convenient for users and effectively prevent pregnancy. The objective of this study was to assess factors associated with unmet need of Long Acting and Permanent Methods of contraception among women in the reproductive age group (15-49) using contraception in health facilities of Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
44
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 8 publications
11
44
1
1
Order By: Relevance
“…However lack of support from husband and fear of side effects are negatively influencing the utilization of long acting and permanent contraceptives. This finding is in agreement with different studies conducted in different parts of Ethiopia [19][20][21]. Similar to the finding from this study Study conducted in public health facilities in Wolayita zone revealed that fear of side effect negatively affects long acting and permanent contraceptive utilization [22].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However lack of support from husband and fear of side effects are negatively influencing the utilization of long acting and permanent contraceptives. This finding is in agreement with different studies conducted in different parts of Ethiopia [19][20][21]. Similar to the finding from this study Study conducted in public health facilities in Wolayita zone revealed that fear of side effect negatively affects long acting and permanent contraceptive utilization [22].…”
Section: Discussionsupporting
confidence: 82%
“…The other major factor for not using long acting contraceptives especially IUCD arises from a nature of providers (being male or female). Many females are not a such comfortable or feel free to receive services like IUCD insertion from male professionals [18][19][20][21].…”
Section: Reproductive Health Characteristics Knowledge and Utilizatimentioning
confidence: 99%
“…In contrast, some studies reported housewife women were more likely to have unmet need of LAPMs (12,34,35).…”
Section: Discussionmentioning
confidence: 91%
“…9,15 Mother attends ANC for 58.3% of the study population/participants. The figure indicates that immense number of mother had ANC attendance not comparable to 22.4% attendance of similar study 13 . Both, this and other indicated study reported as the variable hadn't statistically associated to use of LARC in different study area.…”
Section: Discussionmentioning
confidence: 93%